Analysis of Ozone Technology Interventions for Economic Recovery during the COVID 19 Pandemic: A Case Study of Batu Bara District through Chili Production Center - Nur, Muhammad; Baarri, Ahmad Ni’matullah Al; Sabrina, Tengku; Kusumiyati, Kusumiyati; Fauzi, Ahmad (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The Center for Plasma Research (CPR), Diponegoro University, as the institution that drafted SNI 8759:2019, continues to oversee it implementation. In this paper, we report the successful implementation of SNI 8759:2019 at the chili center in Batu Bara. This success is strongly supported by the producer cooperative "Berkah Abadi Jaya". At the end of May 2021 there will be a chili harvest throughout Indonesia. Chili prices in the Batu Bara chili farming area fell sharply. Chili is bought by a wholesaler for Rp. 7,000.00 per kilogram. The cooperative buys from the farmers as much as Rp. 10,000.00/kg and Rp. 10,500.00/kg and save as much as 835 kg. The collaboration between the research team and the “Berkah Abadi Jaya” Cooperative has synergistically succeeded in applying ozone plasma technology for large-scale chili storage during the main harvest. These saved chilies are resold to the market when prices have improved. The application of plasma ozone technology in chili centers through washing fresh chili grade 1 using ozonized water and storing it in a refrigerator at a temperature of 80 C can extend the shelf life of chilies to 2 months. This application has provided a double benefit for farmers when their crops are purchased by cooperatives. In addition, farmers who are members of the cooperative also benefit by reselling chilies that have been stored at a higher price, which is between Rp. 16,000.00 - Rp. 23,000.00. The quality of chili stored with this technology has been previously investigated by the CPR and examined for confirmation for storage in the chili center of Batu Bara Regency.